Towards a diversified agricultural forest-based economy: Community views of planting sandalwood in Timor-Leste - Thu, Pyone Myat; Barreto, Joaquina; Erskine, William; Williams, Robert; Soares, Abril; Ximenes, Valerio; Ximenes, Anita; Fernandes, Maria; Agostinho, Octaviana P; Page, Tony (Forestry Faculty, Universitas Hasanuddin, 2023)
With growing awareness that export revenues derived from non-renewable oil and gas resources are in decline, Timor-Leste seeks to develop a more sustainable and diversified economy. Sandalwood holds significant cultural, economic and historical importance for the Timorese people, and is representative of an internationally competitive export product. Livelihood diversification can alleviate the prevalence of poverty among smallholders in Timor-Leste. Within this context, and with a focus on forestry, we sought to determine the institutional support and smallholder interest and capacity for restoring over-exploited sandalwood. Interviewed households were acutely aware of the high value and benefits derived from sandalwood and expressed strong interest in planting the species for income generation. Land tenure security, essential for long-term forestry investments, was high among those surveyed and not considered a limitation. Improved forestry extension can address many of the respondent-identified risks which were biophysical (lack of water, pests, livestock, and fire destruction). Legal marketing of planted sandalwood, which is currently prohibited, can help growers maximise benefits from their investments and provide a market signal to stimulate wider planting of sandalwood among smallholders.